Viral encephalitis and seizures cause rapid depletion of neuronal progenitor cells and alter neurogenesis in the adult mouse dentate gyrus - Alberto Pauletti; Polina Gurlo; Edna Weiß; Ana Beatriz DePaula-Silva; Karen S. Wilcox; Sonja Bröer (Frontiers in Cellular Neuroscience)
Infections impacting the central nervous system (CNS) constitute a substantial predisposing factor for the emergence of epileptic seizures. Given that epilepsy conventionally correlates with hippocampal sclerosis and neuronal degeneration, a potentially innovative avenue for therapeutic intervention involves fostering adult neurogenesis, a process primarily occurring within the subgranular zone of the dentate gyrus (DG) through the differentiation of neural stem cells (NSC). While experimental seizures induced by chemoconvulsants or electrical stimulation transiently enhance neurogenesis, the effects of encephalitis and the resultant virus-induced seizures remain inadequately understood. Thus, this study employed the Theiler's Murine Encephalomyelitis Virus (TMEV) model of virus-induced seizures in adult C57BL/6J mice to investigate the impact of infection-induced seizures on neurogenesis at three distinct time points [3, 7, and 14 days post-infection (dpi)]. Immunohistochemical analysis revealed a reduction in the overall number of proliferating cells post-infection. More notably, the specific cell types exhibiting proliferation diverged between TMEV and control (CTR) mice: (1) Neuronal progenitors (doublecortin, DCX+) were almost entirely absent at 3 dpi in the dorsal DG. They resumed proliferation at 14 dpi, but, did not recover to CTR levels, and displayed aberrant migration patterns. (2) The number of proliferating NSCs significantly decreased within the dorsal DG of TMEV mice at 14 dpi compared to CTR, while (3) a heightened population of proliferating astrocytes was observed. Most observed changes were not different between seizing and non-seizing infected mice. In summary, our findings demonstrate that viral infection rapidly depletes neuronal progenitor cells and causes aberrant migration of the remaining ones, potentially contributing to hyperexcitability. Additionally, the increased differentiation toward glial cell fates in infected mice emerges as a possible additional pro-epileptogenic mechanism.